Brain structural thickness and resting state autonomic function in adolescents with major depression. Issue 7 (25th June 2018) - Koenig, Julian; Westlund Schreiner, Melinda; Klimes-Dougan, Bonnie; Ubani, Benjamin; Mueller, Bryon; Kaess, Michael; Cullen, Kathryn R
Abstract: Major depressive disorder (MDD) has been associated with abnormalities in cortical thickness and autonomic function. Adolescence is a time notable for brain development and MDD onset. In healthy adolescents, greater resting state vagal activity (RVA) is associated with lower cortical thickness. The relationship between brain structural thickness and RVA in adolescents with MDD has not previously been studied. This secondary analysis drew on a sample of 37 non-depressed controls and 53 adolescents with MDD. Resting state heart rate and two indices of RVA (HF-HRV and RMSSD) were recorded during a neuroimaging session. Cortical thickness within fronto-limbic regions of interest was measured using Freesurfer analysis of T1-weighted high-resolution structural images. Self-reports of depression severity showed a significant interaction with cortical thickness of the right insula in predicting RMSSD [ t = 2.22, P =0.030, β = 5.44; model fit of the interaction term as indicated by the 'Bayes Factor' (BF): 7.58] and HF-HRV ( t = 2.09, P =0. 041, β = 4.72; BF: 7.94). Clinician ratings of depression severity showed further interactions. Findings underscore the important relationships between RVA and cortical development, suggesting two possible explanations: (i) in adolescent MDD, greater fronto-limbic thickness is compensatory for deficits in autonomic regulation or (ii) increased autonomic arousal results in delayed fronto-limbic maturation. Longitudinal research is necessary to further clarify the nature of the relationship between autonomic functioning and cortical development.